2010
DOI: 10.1016/j.wem.2010.09.008
|View full text |Cite
|
Sign up to set email alerts
|

10% Povidone-Iodine May Be a Practical Field Water Disinfectant

Abstract: The lowest disinfecting concentration of 10% PVI was the 1:1,000 dilution at 15 minutes of contact time. This supports the use of PVI for water disinfection against E. coli, the organism most commonly responsible for traveler's diarrhea. Further studies may assess its effectiveness against more virulent water borne pathogens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…The cumulative mortality rate after the transportation process clarified that the iodine-tranquillized group showed the lowest mortality rate amongst all groups; this could be attributed to the augmented effective role of MS-222 plus the antibacterial effect of iodine which protected fish from accidental bacterial infection during transportation and also decreased the pathogenic bacterial load and improved fish health status. Using iodine at a low dose as 100 ppm for a minimum 10 min of exposure time can effectively destruct germs (OIE 2009;Heiner et al 2010). Chatchawanchonteera et al (2015) reported that povidone-iodine at a dose of 100 ppm for 15-min exposure at 37 °C could inactivate 6 logs of S. agalactiae isolated from fish.…”
Section: Discussionmentioning
confidence: 99%
“…The cumulative mortality rate after the transportation process clarified that the iodine-tranquillized group showed the lowest mortality rate amongst all groups; this could be attributed to the augmented effective role of MS-222 plus the antibacterial effect of iodine which protected fish from accidental bacterial infection during transportation and also decreased the pathogenic bacterial load and improved fish health status. Using iodine at a low dose as 100 ppm for a minimum 10 min of exposure time can effectively destruct germs (OIE 2009;Heiner et al 2010). Chatchawanchonteera et al (2015) reported that povidone-iodine at a dose of 100 ppm for 15-min exposure at 37 °C could inactivate 6 logs of S. agalactiae isolated from fish.…”
Section: Discussionmentioning
confidence: 99%
“…To determine a practical minimal disinfecting concentration for 10% PVI over different contact times and temperatures, Heiner et al 41) exposed Escherchia coli to various dilutions of 10% PVI for 5, 15, and 30 min at 10, 20, and 30 o C, neutralized with 0.5% sodium thiosulfate, and determined mean viable colony forming units (CFUs). In results, no CFUs were observed after exposure to the 1:100 dilutions and after 15 min of exposure to the 1:1,000 dilutions across experimental temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…A 10% PVP-iodine was tested at various dilutions as an agent for field water disinfection against E. coli [91]. Optimal conditions for suppressing E. coli colony formation were identified as a 1 : 1000 dilution of 10% PVP-iodine, a contact time of 15 min, and a temperature of 10-30°C.…”
Section: Applications Of Polymeric Iodophorsmentioning
confidence: 99%